Students’ anxiety and attitudes towards writing at Sekolah Menengah Kebangsaan Sungai Baging - Mohd Hasharudin, Che Shamsudin; Hafizoah, Kassim; Abdullah Adnan, Mohamed (Universiti Malaysia Pahang, 2025)
This study examined the challenges faced by rural secondary school students in writing, focusing primarily on their anxiety and attitudes towards this skill. Grounded in Krashen’s Affective Filter Hypothesis, it examined how affective factors, such as anxiety and attitudes, influence second language writing performance. Local secondary students, particularly those in remote areas, often encounter difficulties in English writing, largely due to anxiety and negative attitudes that impede their performance and motivation. Therefore, exploring ways to address these emotional challenges is indispensable for enhancing writing outcomes, as recognising students’ anxiety can improve writing instruction and foster a supportive classroom environment. A quantitative survey design was utilised, focusing on three key aspects: variations in writing anxiety by gender, proficiency, and educational level; differences in attitudes towards writing; and the correlation between writing attitudes and anxiety. A 40-item, five-point Likert scale agreement questionnaire was adapted and distributed to 300 students aged between 12 and 17 years from SMK Sungai Baging, Kuantan. Results were analysed using an independent samples t-test and Pearson correlation coefficient. Results indicated moderate levels of writing anxiety and attitudes, revealing a significant positive correlation between anxiety and attitudes. Higher levels of anxiety and negative attitudes were associated with low self-confidence and diminished creativity. Consequently, writing classes should incorporate engaging activities and constructive feedback to foster positive attitudes and alleviate anxiety. Further in-depth research is recommended with larger samples, particularly in Malaysian rural secondary schools.